Consensus of the Brazilian Headache Society (SBCe) for prophylactic treatment of episodic migraine: part II - Santos, Paulo Sergio Faro; Melhado, Eliana Meire; Kaup, Alexandre Ottoni; Costa, Aline Turbino Neves Martins da; Roesler, Célia Aparecida de Paula; Piovesan, Élcio Juliato; Sarmento, Elder Machado; Theotonio, Giselle Oliveira Martins; Campos, Henrique Carneiro de; Fortini, Ida; Souza, Jano Alves de; Júnior, Jayme Antunes Maciel; Segundo, João Batista Alves; Carvalho, João José Freitas de; Speziali, José Geraldo; Calia, Leandro Cortoni; Barea, Liselotte Menke; Queiroz, Luiz Paulo; Souza, Marcio Nattan Portes; Figueiredo, Marcos Ravi Cerqueira Ferreira; Costa, Maria Eduarda Nobre de Magalhães; Peres, Mário Fernando Prieto; Jurno, Mauro Eduardo; Peixoto, Patrícia Machado; Kowacs, Pedro André; Rocha-Filho, Pedro Augusto Sampaio; Filho, Pedro Ferreira Moreira; Silva-Neto, Raimundo Pereira; Fragoso, Yara Dadalti (Arquivos de Neuro-Psiquiatria, 2022)
Background Migraine affects 1 billion people worldwide and > 30 million Brazilians; besides, it is an underdiagnosed and undertreated disorder.Objective The need to disseminate knowledge about the prophylactic treatment of migraine is known, so the Brazilian Headache Society (SBCe, in the Portuguese acronym) appointed a committee of authors with the objective of establishing a consensus with recommendations on the prophylactic treatment of episodic migraine based on articles from the world literature as well as from personal experience.Methods Meetings were held entirely online, with the participation of 12 groups that reviewed and wrote about the pharmacological categories of drugs and, at the end, met to read and finish the document. The drug classes studied in part II of this Consensus were: antihypertensives, selective serotonin reuptake inhibitors, serotonin and norepinephrine reuptake inhibitors, calcium channel blockers, other drugs, and rational polytherapy.Results From this list of drugs, only candesartan has been established as effective in controlling episodic migraine. Flunarizine, venlafaxine, duloxetine, and pizotifen were defined as likely to be effective, while lisinopril, enalapril, escitalopram, fluvoxamine, quetiapine, atorvastatin, simvastatin, cyproheptadine, and melatonin were possibly effective in prophylaxis of the disease.Conclusions Despite an effort by the scientific community to find really effective drugs in the treatment of migraine, given the large number of drugs tested for this purpose, we still have few therapeutic options.
Keywords: Cefaleia Histamínica; Enxaqueca Sem Aura; Consenso; Medicina Preventiva